The Effects and Mechanisms of Exercise on the Treatment of Depression - Xie, Yumeng; Wu, Zuotian; Sun, Limin; Zhou, Lin; Wang, Gaohua; Xiao, Ling; Wang, Huiling (Frontiers in Psychiatry, 2021)
Background: It is necessary to seek for alternative therapies for depression, as side effects lead to poor adherence to medications and some patients do not achieve a clinical treatment effect. Recently the role of exercise as a low-cost and easy-to-use treatment of depression is gaining attention with a number of studies having shown that exercise is effective on reducing depressive symptoms and improving body functions such as cardiorespiratory system and cognitive function. Because of a heterogeneity of exercise therapy programs, there is no standardized and unified program; Few studies summarize the specific properties of exercise programs (type, intensity, duration, frequency) and clinical prescriptions for exercise are not mentioned in most articles. Aims: This paper aims to investigate the feasibility and efficacy of exercise therapy for patients with depression, in order to appraise the evidence and outline accepted guidelines to direct individualized treatment plans for patients with depression based on their individual situations. Methods: A systematic review of English language literature including papers published from 2010 to present in Pubmed is performed. Based on the fact that it is feasible to prescribe exercise therapy to patients with depression, nearly three years of clinical studies on the treatments of depressive symptoms by exercise are firstly reviewed, compared the exercise programs utilized. Conclusions: Exercise has therapeutic effects on depression of all age groups (mostly 18-65 years old), as a single therapy, an adjuvant therapy or combination therapy, and the benefits of exercise therapy are comparable to traditional treatments for depression. Moderate intensity exercise is enough to reduce depressive symptoms, but higher doses are better for overall functioning. Exercise therapy has become more widely used because of its benefits to the cardiovascular system, emotional state and systemic functions. Recommendations: Aerobic exercise/mind-body exercise (three-five sessions per week with moderate intensity lasting for 4-16 weeks) is recommended. Individualized protocol in the form of group exercise with supervision is effective to increase adherence to treatment.